Dampingan Pembuatan Digital Payment (QRIS) Bagi UMKM dalam Mendukung Transaksi di Desa Cendoro Kecamatan Palang Kabupaten Tuban - Eny Latifah; Suroso Suroso; Putra Andika Yoga Pratama; Ghulam Asy Syah’Bany; Inne Zulistiani; Khoirul Ummah; Wilda Roisyatul Hifdiyah; Rika Nur Amelia; Rofiqo Afiyati (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
The digital era presents challenges as well as opportunities for business actors, especially Micro, Small, and Medium Enterprises (MSMEs). Accelerating the adoption of digital technology-based payment systems is an urgent need so that MSMEs are able to compete and improve transaction efficiency. This Community Service (PKM) activity was carried out in Cendoro Village, Tuban Regency, with the aim of providing assistance to MSME actors through the implementation of a QRIS-based digital payment system. The method of implementing PKM consists of three stages, namely preparation, implementation, and evaluation. In the preparation stage, needs are identified and socialization of QRIS benefits are carried out. The implementation stage includes technical training on the use of QRIS as well as direct assistance in the implementation of non-cash transactions. The evaluation stage was carried out to measure the level of understanding and application of QRIS by participants. The results of the activity showed that participants understood the concept of digital payment and were able to apply QRIS in daily transactions. In addition, this activity encourages an increase in the adoption of QRIS which has an impact on efficiency, transaction security, expansion of market access, and local economic growth. The main obstacles faced include limited technological knowledge, uneven internet access, and operational costs. Thus, this PKM contributes to strengthening digital literacy and supporting technology-based economic transformation in Cendoro Village, Tuban Regency.